2013
DOI: 10.1002/hep.26372
|View full text |Cite
|
Sign up to set email alerts
|

An unbalance between von Willebrand factor and ADAMTS13 in acute liver failure: Implications for hemostasis and clinical outcome

Abstract: Emerging evidence supports the concept of a rebalanced hemostatic state in liver disease as a result of a commensurate decline in prohemostatic and antihemostatic drivers. In the present study, we assessed levels and functionality of the platelet-adhesive protein von Willebrand factor (VWF) and its cleaving protease ADAMTS13 in the plasma of patients with acute liver injury and acute liver failure (ALI/ALF). Furthermore, we explored possible associations between VWF, ADAMTS13, and disease outcome. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
200
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(211 citation statements)
references
References 35 publications
5
200
0
2
Order By: Relevance
“…These observations provide an explanation of the deleterious UL-VWFM effects on severe liver injury progression. Conversely, Hugenholtz et al (9) reported that UL-VWFM proportion was reduced in spite of markedly low ADAMTS13:AC in AH and ALF patients. They explained this discrepancy from the action of other proteases on VWF and/or the effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations provide an explanation of the deleterious UL-VWFM effects on severe liver injury progression. Conversely, Hugenholtz et al (9) reported that UL-VWFM proportion was reduced in spite of markedly low ADAMTS13:AC in AH and ALF patients. They explained this discrepancy from the action of other proteases on VWF and/or the effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hugenholtz et al (9) reported low ADAMTS13:AC and high VWF:Ag in AH and ALF patients. However, they stated that low ADAMTS13:AC, but not high VWF:Ag, was associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet hyperactivity has also been reported in patients with cholestatic liver disease [12,42] . A prothrombotic state has been reported in acute liver injury based on an imbalance between vWF/ADAMTS13, intact thrombin generation, and high levels of PAI-1 [28,69,70] . Minimal effects on haemostasis are assessed by thromboelastography in these patients [71] , despite the severe derangement shown by standard coagulation tests.…”
Section: Fibrinolysis Testsmentioning
confidence: 99%
“…1 In addition, chronic and acute liver diseases are characterized by chronic endothelial cell activation resulting in additional hemostatic changes such as substantially elevated plasma levels of von Willebrand factor (VWF). 2,3 Finally, systemic or intrahepatic activation of coagulation results in consumption of platelets and hemostatic proteins. 4,5 These hemostatic changes accompanying liver diseases are among the most complex acquired hemostatic changes, and the net effects of these changes have, therefore, long been unclear.…”
mentioning
confidence: 99%